Evaluation of The Manitoba Healthy Baby Prenatal Benefit: Is It Improving Birth and Early Childhood Outcomes for Metis Families? - Brownell, Marni; Sanguins, Julianne; Chartier, Mariette; Nickel, Nathan; Enns, Jennifer; Chateau, Dan; Burland, Elaine; Sarkar, Joykrishna; Lee, Janelle Boram; Struck, Shannon; Hinds, Aynslie; Quddus, Farzana; et al. (International Journal of Population Data Science, 2020)
Introduction In Manitoba, low-income pregnant women are eligible for the Healthy Baby Prenatal Benefit (HBPB), a prenatal income supplement. Research has demonstrated positive outcomes associated with HBPB, but it remains unknown if Metis women and children – who are of mixed European and Aboriginal descent and one of the most marginalized populations in Canada -- benefit from the program. Objectives and Approach The Manitoba Metis Federation and the Manitoba Centre for Health Policy partnered to determine the impact of HBPB on Metis newborn and early childhood outcomes. We included all Metis women giving birth in Manitoba 2003-2011 who received income assistance during pregnancy (n=4,852), adjusting for differences between those receiving (n=3,681) and not receiving (n=1,171) HBPB with propensity score weighting. We used multi-variable regressions to compare outcomes between groups: breastfeeding initiation, low birth weight, preterm birth, small- and large-for-gestational age, Apgar scores, birth hospitalization length of stay (LOS), neonatal readmissions, infant hospitalizations, vaccinations at age 1 and 2, and child development scores at kindergarten. Results HBPB receipt was associated with reductions in low birth weight (adjusted Relative Risk (aRR): 0.74 (95% CI: 0.58-0.94)) and preterm births (aRR: 0.78 (0.65-0.94)), and increases large-for-gestational age births (aRR: 1.21 (1.06-1.39)) and neonatal readmissions (aRR: 1.58 (1.05-2.37)). Birth hospitalization LOS was lower for newborns whose mothers received HBPB (Mean Difference 0.29 days). HBPB was associated with increases in vaccinations for children aged 1 (aRR: 1.08 (1.00-1.15)) and 2 (aRR: 1.12 (1.05-1.18)). No significant associations were found for small-for-gestational age births, Apgar scores, breastfeeding initiation, infant hospitalizations or child development scores. Conclusion / Implications A modest unconditional prenatal income supplement to low-income Metis women was associated with improved birth outcomes and child vaccinations; however, an association with increased neonatal readmissions warrants further exploration. Lack of significant associations between HBPB and child development measures suggests more sustained support may be necessary to improve longer-term outcomes.